Menjangkau Pedalaman Lewat Misi Kontekstual Gereja sebagai Mitra Allah Menggenapi Janji Bagi Bangsa - Matius Kalatiku (Sekolah Tinggi Teologia Kerusso Indonesia, 2025)
This article discusses the role of the church in reaching remote communities in Indonesia through a contextual mission approach. Using a qualitative-descriptive method based on literature review and theological narrative reflection, the study finds that effective church mission must be incarnational, holistic, and collaborative. The church is called to be God's partner in bringing the liberating Gospel into the socio-cultural context of local communities. Contextual approaches are key to successful ministry, supported by the use of technology and inter-institutional synergy. This study recommends renewing the church’s mission vision and theological education to meet contemporary challenges in rural and remote mission work.